Ethanol content of beverages and condiments in Malaysia - Law, Se Vern; Mat Hashim, Dzulkifly; Abu Bakar, Fatimah; Radi, Nurul Aimi (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The study involved the detection of the ethanol content of various market food and beverage products. The objectives of this study are to identify the food products that contain ethanol and to quantify the percentage of ethanol present. Headspace Gas Chromatography-Mass Spectrometer (HS-GC-MS) was used to screen the samples for detection of ethanol and further quantification.Samples were purchased from several hypermarkets in the Klang Valley and Selangor. A total of 119 samples, including fermented and cultured beverages, carbonated drinks, juices and cordials,tea and coffee, energy drinks, colouring and flavourings, vinegars and sauces were analyzed. Of the total number of samples screened, 58 were found to contain ethanol. The ethanol content in the samples ranged from 0.001% to 3.510%. The Headspace method is proven to be an effective and reliable methof for the detection of low alcohol concentrations by minimizing the loss of the ethanol compound during sample preparation and extraction. Ethanol is present due to natural fermentation of the product or added as solvent during production.